A strategic approach for tongue reconstruction to achieve predictable and improved functional and aesthetic outcomes - Engel, Holger; Huang, Jung Ju; Lin, Chia-Yu; Lam, Weeleon; Kao, Huang-Kai; Gazyakan, Emre; Cheng, Ming-Huei (Plastic and reconstructive surgery, 2010)
Background: Successful tongue reconstruction should restore swallowing, speech function, and cosmesis. The purpose of this prospective study was to evaluate the functional and aesthetic outcomes of tongue reconstruction using variable free flaps based on different tongue defects. - Methods: One hundred four patients with a mean age of 49 ± 11 years underwent free tissue transfer following resection of T2 to T4 tongue cancers. The defects were classified prospectively into three groups: group A, hemiglossectomy defects (n = 42) reconstructed with 33 radial forearm flaps and nine anterolateral thigh perforator flaps; group B, subtotal glossectomy defects (n = 50) reconstructed with anterolateral thigh perforator (n = 44) or anterolateral thigh myocutaneous flaps (n = 6); and group C, total glossectomy defects (n = 12) reconstructed with 12 pentagonal anterolateral thigh myocutaneous flaps. - Results: Two flaps failed, giving a success rate of 98.1 percent. Two patients developed partial flap loss. At a mean follow-up of 46.2 months, 33 patients were available for evaluation. Normal speech was found in 13 patients, intelligible speech was found in nine, and slurred speech was found in 11. Sixteen patients could eat a normal diet, eight could eat a soft diet, seven could eat a liquid diet, and two required tube feeding (p = 0.28). The cosmetic results were rated as excellent in 19, good in nine, and fair in five patients (p = 0.76). - Conclusions: A strategic approach of variable flap selections based on different tongue defects may achieve predictably better functional and aesthetic outcomes. The innovative pentagonal anterolateral thigh myocutaneous flap for total tongue reconstruction creates a free neotongue tip with adequate volume, producing acceptable swallowing function and cosmesis.
Gesehen am 16.03.2023